Organic geochemical characteristics of black shales across the Ordovician–Silurian boundary in the Holy Cross Mountains, central Poland. (September 2015) - Mustafa, Karwan A.; Sephton, Mark A.; Watson, Jonathan S.; Spathopoulos, Fivos; Krzywiec, Piotr
Abstract: Black shales in the Holy Cross Mountains area of Poland provide a record of environmental change across the Ordovician–Silurian boundary. The changing depositional conditions have generated a variation in organic matter contents above and below the boundary. Investigating the organic constitution of these black shales has the potential to reveal how their organic matter contents were generated and how suitable these rocks and their lateral equivalents may be for exploitation as shale gas reservoirs. One outcrop at the Holy Cross Mountains with a continuous section across the Ordovician–Silurian boundary occurs near the village of Bardo Stawy in the Kielce region, and contains sandy-silty mudstones, as well as grey and black shales. Organic geochemical analyses of samples at Bardo Stawy reveals low Total Organic Carbon (TOC) contents for Ordovician samples and higher TOC values for Silurian samples. Organic biomarkers indicate that the Ordovician rocks were deposited in a shallow-marine shelf setting, while the Silurian rocks were deposited in a deeper marine environment. The progressive increase in TOC from the uppermost Ordovician to the lowermost Silurian rocks reflects increasingly oxygen-poor depositional conditions during the post-glacial transgression. Following the deposition and preservation of organic matter in the Ordovician and Silurian rocks, these rocks were buried and subjected to thermal maturation. Rock Eval and biomarker thermal maturity parameters all indicate that the organic matter is mature and lies within the oil window. The Ordovician and Silurian shales have direct relevance to recent attempts to discover and exploit shale gas reservoirs in Poland. Our data and interpretations suggest that the relatively low TOC values (<2%) and low maturities for gas generation render these rocks unsuitable for commercial shale gas production. The progressive improvement in conditions for preserving organic matter across the Ordovician–Silurian boundary does, however, leave the possibility that more suitable deposits occur in Early Silurian rocks in the other parts of the basin. Highlights: TOC and biomarker changes across the Ordovician–Silurian boundary were studied. Ordovician and Silurian paleoenvironments were reconstructed. Sea level rise and upwelling led to TOC enrichment in the Early Silurian. Limited potential for shale gas production in the Bardo Stawy samples. Lateral equivalent black shales may have potential for shale gas production.